Migration, Regionalism, and the Ethnic Other, 1840-1870 - Joranger, Terje Hasle (American Studies in Scandinavia, 2016)
This article shows accounts of Norwegian immigrants and their encounter with various ethnic groups in America including Native Americans, African-Americans, Chinese, Irish, and Yankees in the period between 1840 and 1870. The article presents several regions in the United States, namely the Upper Midwest, Texas, and California. The use of primary source material including newspapers, guidebooks and letters provide good insights into thoughts and attitudes, and not the least prejudice, among this Old immigrant group toward the ethnic “Other.” The Norwegian immigrant group aimed at becoming good citizens through a negotiating process between the group, the dominant native-born American group and other ethnic groups in the United States. By characterizing several other ethnic groups based on race, Norwegian-Americans employed whiteness in a double negotiation, both tied to the creation of a Norwegian-American identity and in finding their place in the social hierarchy in America.